Limonologia e qualidade ambiental de um corpo lêntico receptor de efluentes tratados da indústria de petróleo - Lima, Anita Maria de (2004)
Environmental pollution has become a subject of public interest throughout the world. Not only have developed countries been affected by environmental problems but also the developing nations have started to suffer from the serious impacts of pollution. Within this context it is necessary to collect simplified environmental data to assist in the management of water resources by the appropriate authorities. These data are obtained through an environmental index that allows a space-time comparison of points distributed in the same aquatic body, or between different water bodies, for physico-chemical and bacteriological parameters. The aim of this present study was to determine the environmental status of the Lagoa de Baixo at Guamaré/RN, where a production unit of PETROBRAS RN/CE is located. For this purpose the Water Quality Index (WQI) was used in both an add and multiply form, the Trophic State Index (TSI) and the Environmental Quality Quotient (EQQ), as well as determining the concentrations of metals. The average values obtained for the WQI, in its two forms were 68,67 and 62,76 respectively which were inside the good qualification. According to the TSI the lagoon showed characteristics of a middle trophic state, and an impact level of regular as determined by the EQQ